2006
DOI: 10.1016/j.meatsci.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological characterization of alheira: A typical Portuguese fermented sausage with particular reference to factors relating to food safety

Abstract: Alheiras are traditional smoked naturally fermented meat sausages produced in the north of Portugal. They have not previously been characterized as to their chemical and microbiological status. pH and salt levels are insufficient to assure microbiological safety, there is ample opportunity for post-cooking contamination; the products require chill storage and cooking before consumption. Heavy metals and biogenic amines were, in general, within accepted limits for meat products. Lactic acid bacteria comprised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 17 publications
7
61
3
Order By: Relevance
“…Re-appearance of yeasts and molds was observed after 30 days of storage to reach 3log cfu g -1 . We think that these bacteria groups might play an important role in the definition of the organoleptic profile of the final product as reported for several traditional meat products [24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Re-appearance of yeasts and molds was observed after 30 days of storage to reach 3log cfu g -1 . We think that these bacteria groups might play an important role in the definition of the organoleptic profile of the final product as reported for several traditional meat products [24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid bacteria enhance the physico-chemical properties of sausages and restrict the growth of some undesirable microorganisms (Gonzales and Diez 2002;Samelis et al, 1998). Ferreira et al, (2006) indicated that fermented sausages are considered safe foods due to the reduction in water activity and pH that occurs during processing and storage and inhibits the development of pathogenic bacteria.…”
mentioning
confidence: 99%
“…Phenylethylamine results from phenylalanine decarboxylation, and it is commonly present in fermented meat products containing high quantities of tyramine (1,8). Due to their vasoactive properties, tyramine and phenylethylamine are regarded as undesirable compounds that may cause health disruptions to sensitive consumers, especially to those under treatment with certain drugs, such as mono-amine oxidase inhibitors (27).…”
mentioning
confidence: 99%